Improved calculations for no-load transformer switching surges. - Popov, M.
This paper deals with a modeling of components and calculation of transient overvoltages that build up on the transformer primary terminals after the transformer has been switched off by a vacuum circuit breaker (VCB). The transformer is connected to the circuit breaker by a cable. The transient overvoltages are calculated for different cable lengths, and the cumulative probability of different arc angles is investigated. In this study two cases are considered: transient overvoltages due to steady-state magnetizing current switching, and transient overvoltages due to inrush current switching. It is shown that the case of inrush current switching is worse, as virtual current chopping is possible. The cable is modeled by pi sections, whereas the transformer model is based on a terminal impedance. The VCB re-ignitions are modeled by means of withstand voltage characteristics and high-frequency quenching capability. Due to shortage of field tests, this work uses only literature references to compare the results with actual measurements
Keywords: Arc angles; Cable lengths; Cumulative probability; High-frequency quenching capability; Inrush current switching; No-load transformer switching surges; Re-ignitions.; Steady-state magnetizing current switching; Terminal impedance; Transformer model; Transformer primary terminals; Transient overvoltages; Vacuum circuit breaker; Virtual current chopping; Withstand voltage characteristics